Knowledge needs and use in long‐term care homes for older people: A qualitative interview study of managers' views. (22nd September 2020) - Day, Jo; Dean, Sarah G; Reed, Nigel; Hazell, Jan; Lang, Iain
Abstract: We explore the views of managers' knowledge needs and use to optimise care practices and enhance the life experience for older people living, and staff working, in long‐term care homes (with and without nursing). This paper contributes to previous research by offering insights into the knowledge types drawn upon and used by managers to inform efforts to better support gaining and mobilising knowledge. Using a pragmatic qualitative approach, we undertook 19 semi‐structured interviews with managers and leaders in 15 care homes in the South West of England, varying in geographical location, size and type of ownership. We did a thematic analysis of the data using Framework Analysis. Our interpretations were informed by the existing literature on knowledge types. We identified three themes from our analysis as to managers' knowledge needs and use when implementing changes. First, views about training and formal reports or "explicit knowledge" consisting of the two sub‐themes "gaining explicit knowledge" and "research knowledge". Second, perspectives relating to practical experience or "tacit knowledge" and judging the use of knowledge in particular cases or "phronesis". Third, the role of emotion in managers' knowledge needs and use. We found that having knowledge was positively valued by managers and leaders for improving care practices and enhancing the lives of people residing in care homes. Tacit knowledge and phronesis were particularly highly valued and we note challenges with the perceived applicability, relevance and use of research evidence. We identify that emotions are an important component within knowledge use and a need to further understand how to support the emotional wellbeing of managers so they can support care staff and residents. Greater consideration is needed as to how to optimise gaining and mobilising all knowledge types ‐ "know‐what, " "know‐how, " "know‐when" and "know‐feel" ‐ to benefit people living, and staff working, in care homes.